(untitled) (Journal of the College of Languages (JCL), 2021)
The present paper sheds light on the psychological structure of Simha Bin Zion’s A Broken Soul. After reviewing the biography of the storyteller, it is clear that the hero of the rebellious character in the story of (A Broken Soul) is the writer himself. The storyteller directly begins to depict his psychological sufferings in his childhood days. He tells a story full of sadness and refusal of the neglect he suffered in his childhood. It is obvious that the early five years of Samha bin Zion’s life is considered a period of conflict that participated in the formation of his individual identity. The story represents an outlet for a hidden secret world buried under the layers of his consciousness. It deals with the dark and dark side of the life of a Jewish boy in the Diaspora, and the tragic existence full of restrictions represented by the cruelty of the strict educational system in Al-Haidar; (the Jewish religious school) where Samha bin Zion was a neglected child and a victim of the father’s control at home and the teacher in school. The aim behind such a rigid way of education is to bring him to the inelastic Jewish conventions. At his present stage of contemplation and after a long search for his true self, the writer reveals the frustration and instability he suffered. In short, the paper discusses the suffering of the writer’s personal conditions that enhanced his deep psychological problem, and helped to make him a great story teller. תקציר העיון הזה עוסק במבנה הפסיכולוגי של שמחה בן ציון בסיפורו נפש רצוצה כדוגמה. ראוי לציין, הסופרים העבריים משתמשים באמצעים ספרותיים שונים לבטא את דיעותיהם שמשקפות את השקפותיהם בדבר עצמם,גם הסופר בוחר השיטה המתאימה לו לפי הלך נפשו ויכולתו האמנותית. בסיפור זה שמחן בן ציון מתאר את זכרונות ילדותו המתקשרים בנפש רצוצה. ונושא הסיפור הרודים בנער במקל וברצועה, ועליו לעמוד בפני עינויים אלה, וכך הוא נדחק ונלחץ לצדדים רבים, כאן הופיע המספר לפנינו, הריאליסטי החותך אל האמת הקודרת של החיים ומרידות המציאות, וכך מתבלטת בין שורות סיפורו נשמתו הצועקת מרד על המתחולל בעולמו ויגונו עולה מבין התיאורים האכזריים הריאליים. בסיפורו הגדול והחשוב ביותר מתאר שמחה בן ציון את חיי ילד העברי בבית אבא ובחדר עם בסיס נסיונו וזכרונותיו הוא החינוך הפגום המעציבות. חינוך החדר ובית האב הוא עתיד למרוד בתורת הורים ומורים, ובמלמדים האישיים, חיים אילו רדופים בעינויים, משבירים, שאיפות ותקווה לתמודה, וגם במחקר הזה טיפלנו בחייו של הסופר בקצור וגם ביצירותו באופן כללי. המחקר הזה עוסק באחד מהסופרים שנחשבו בעלי – השפעה בתהליך הספרות העברית החדשה ,וגם במחקר הזה טיפלנו בחייו של המספר בקצור וגם ביצירותו באופן כללי, העיון הזה ביקורת למלמודים של החדר בסיפורו של שמחן בן ציון. וגם הבהרת של הקונפליקט הפסיכולוגי של המספר. לפי אופי העיון השתמשנו בשיטה הפסיכולוגית, כי השיטה הפסיכולוגית מקשרת בין האוטוביוגרפיה של הסופר וישיותו . הבעיה העיקרית במחקר היא התשובה על שאלה חשובה מה הוא המניע מאוחורי כתיבת סיפור "נפש רצוצה". האם יש יחס בין המבנה הפסיכולוגי של ’שמחה בן ציון’ לבין הספרות.